2011
DOI: 10.1007/s11269-011-9794-1
|View full text |Cite
|
Sign up to set email alerts
|

Membrane Process Design for the Reduction of Wastewater Color of the Mazandaran Pulp-Paper Industry, Iran

Abstract: The aim of this study is evaluate the use of membrane bioreactor for wastewater treatment Mazandaran pulp and paper Industry. The qualification of wastewater is case study and Characteristics of this industry wastewater were determined by different experiments such as: COD, BOD, Color, densitometry, viscometry and TG/DTA analyzer. Also, the color creating agents in the investigated wastewater was characterized. Then In this study, flux, retention, and permeate quality of various Nanofiltration and low-pressure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
11
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 7 publications
(6 reference statements)
0
11
0
Order By: Relevance
“…They have been used in some P&P industry applications where the goal is to desalinate the water, in addition to removing other contaminants (Zhang et al 2009;Khosravi et al 2011;Li and Zhang 2011;Sheldon et al 2012;Saif et al 2013; Ordóñez et al 2013). For instance, Khosravi et al (2011) demonstrated the use of an RO system in removing color and oxygen demand from P&P mill effluent. The permeate flux was low, but the resulting water quality was distinctly higher than what was achieved in parallel tests involving nanofiltration.…”
Section: Membrane Filtrationmentioning
confidence: 99%
See 4 more Smart Citations
“…They have been used in some P&P industry applications where the goal is to desalinate the water, in addition to removing other contaminants (Zhang et al 2009;Khosravi et al 2011;Li and Zhang 2011;Sheldon et al 2012;Saif et al 2013; Ordóñez et al 2013). For instance, Khosravi et al (2011) demonstrated the use of an RO system in removing color and oxygen demand from P&P mill effluent. The permeate flux was low, but the resulting water quality was distinctly higher than what was achieved in parallel tests involving nanofiltration.…”
Section: Membrane Filtrationmentioning
confidence: 99%
“…Thus, the permeate can be used as intake water for a paper mill, making it possible to run the operation with close to zero liquid effluent (Pizzichini et al 2005;Khosravi et al 2011;Hermosilla et al 2012a;Saif et al 2013). Sierka et al (1997), Zhang et al (2009), andBennani et al (2012) evaluated systems in which nanofiltration was used as a preliminary step before reverse osmosis separation of paper industry wastewater, reporting almost complete removal of solutes.…”
Section: Membrane Polishing Filtrationmentioning
confidence: 99%
See 3 more Smart Citations